Omega-3 supplementation in young offenders: a randomized, stratified, double-blind, placebo-controlled, parallel-group trial - Raine, Adrian (Journal of experimental criminology, 2020)
To examine whether omega-3 supplementation reduces antisocial and aggressive behavior in offenders.